2019
DOI: 10.3892/ol.2019.10554
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of lncRNA GATA6‑AS suppresses the migration and invasion of cervical squamous cell carcinoma by downregulating MTK‑1

Abstract: The diagnosis and treatment of cervical squamous cell carcinoma is challenged by difficulties in the determination of tumor invasion. GATA binding protein 6 antisense (GATA6-AS) is a recently identified long non-coding RNA that exhibits critical functions in the growth of endothelial cells; however, to the best of our knowledge, its involvement in other physiological and pathological processes is unknown. By reverse transcription-quantitative polymerase chain reaction, the present study examined the expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
(28 reference statements)
0
4
0
Order By: Relevance
“…Conversely, growth arrest associated lncRNA 1 (GASL1) has been reported to be significantly downregulated in GC tissues and to inhibit GC cell proliferation and tumor growth by inactivating the Wnt/β-catenin signaling pathway [13]. Emerging studies show that antisense lncRNAs (lncRNAs-AS) can modulate cancer progression by functioning as positive or negative regulators of coding genes [14][15][16][17]. Tumor protein translationally controlled 1 antisense RNA 1 (TPT1-AS1) has been studied by Jiang et al who showed that TPT1-AS1 as an oncogenic lncRNA promotes cell growth and metastasis in cervical cancer [18], as well as by Wu et al who further revealed that ectopic TPT1-AS1 expression is strongly associated with unfavorable epithelial ovarian cancer (EOC) clinicopathological features and induces EOC tumor growth and metastasis [19].…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, growth arrest associated lncRNA 1 (GASL1) has been reported to be significantly downregulated in GC tissues and to inhibit GC cell proliferation and tumor growth by inactivating the Wnt/β-catenin signaling pathway [13]. Emerging studies show that antisense lncRNAs (lncRNAs-AS) can modulate cancer progression by functioning as positive or negative regulators of coding genes [14][15][16][17]. Tumor protein translationally controlled 1 antisense RNA 1 (TPT1-AS1) has been studied by Jiang et al who showed that TPT1-AS1 as an oncogenic lncRNA promotes cell growth and metastasis in cervical cancer [18], as well as by Wu et al who further revealed that ectopic TPT1-AS1 expression is strongly associated with unfavorable epithelial ovarian cancer (EOC) clinicopathological features and induces EOC tumor growth and metastasis [19].…”
Section: Introductionmentioning
confidence: 99%
“…A recently discovered lncRNA, GATA binding protein 6 antisense (GATA6-AS), is downregulated in the tumor tissues of cervical squamous cell carcinoma patients. According to this study, MAP3K4 is downregulated when GATA6-AS is expressed, hindering cancer cells from migrating and invading [ 85 ]. With a similar mechanism, the long non-coding RNA-OIS1 inhibits HPV-positive, but not HPV-negative cervical squamous cell carcinoma by upregulating MAP3K4 [ 86 ].…”
Section: The Complex Function Of Map3k4 Concerning Tumormentioning
confidence: 99%
“…Accordingly, OIS1 overexpression markedly reduced the proliferation of the HPV-positive SiHa cells, potentially by inhibiting the expression of the mitogen-activated protein kinase kinase kinase 4 (MTK-1) [90]. MTK-1 expression was also reduced following GATA binding protein 6 antisense (GATA6-AS) overexpression in CSCC cell lines; however, GATA6-AS expression levels were revealed to be significantly reduced in both HPV-positive and -negative CSCC patients, suggesting GATA6-AS might play a role in CSCC through an HPV-independent pathway [128]. The study of Wang et al, that was already discussed above, reported 19 lncRNAs that were differentially expressed between HPV-positive CSCC and adjacent non-tumor tissues, and the co-expression network and function prediction suggested that all of them could play a role in HPV-driven CSCC [100].…”
Section: Csccmentioning
confidence: 99%